Public management and complexity theory : richer decision-making in public services - Rhodes, Mary Lee (Routledge critical studies in public management, 2011)
That public services exhibit unpredictability, novelty and, on occasion, chaos, is an observation with which even a casual observer would agree. Existing theoretical frameworks in public management fail to address these features, relying more heavily on attempts to eliminate unpredictability through increased reliance on measurable performance objectives, improved financial and human resource management techniques, decentralisation of authority and accountability and resolving principal-agent behaviour pathologies.